Effects of a mental health promotion and mental health prevention program on stress and depression among first-year nursing students - Karseewong, wiramon; Kongthanachayopit, Suprawee (Journal of Nursing, Siam University, 2022)
Objective To study 1) The basic information on the mental health status of first-year nursing students 2) The program for mental health promotion and prevention among first-year nursing students 3) Comparing The effect of the program a mental health promotion before and after using The program for mental health promotion and prevention among first-year nursing students. Method Quasi-experimental research One Group Pretest – Posttest Design. It was conducted in 2 phases, the first phase was to study the basic information on mental health status and developed mental health promotion and prevention among first-year nursing students and the second phase was a trial of the program. The study was conducted from August - December 2021. Results The mental health status of 175 first-year nursing students by using the Suan Prung Stress Assessment found that 31.43% had a high level of stress. There was severe stress at 20.0% and survey depression using the CES-D Depression Scale. (Center for Epidemiologic Studies-Depression Scale). The study found that nursing students have depression 14.29%. In the program mental health promotion model to prevent mental problems among first-year nursing students that there were 3 steps Step 1: Survey and screening for mental problems. Step 2: Organizing activities to promote mental health to prevent mental problems. Step 3: Evaluate the performance. Results in phase 2, the trial of a mental health promotion model to prevent mental problems among nursing students. The sample consisted of 23 nursing students with mental health problems. The differences between stress and depression were analyzed before and after participating in the activities the statistic was used paired t-test. It was found that the difference was statistically significant at p ˂ 0.05. The stress before participating in the activity averaged a score of 66.48. After participating in the activity, there was an average score of 38.21. The average pre-activity depression score was 23.04. After participating in the activity, there was an average score of 9.52. Conclusion The mental health care for first-year nursing students should be organized by screening for mental problems, organizing activities to promote and prevent mental problems, and continuous monitoring and evaluation.